PERBANDINGAN SKOR DEPRESI ANTARA PASIEN DIABETES MELITUS DENGAN PASIEN KAKI DIABETIKUM DI RSUD RADEN MATTAHER JAMBI TAHUN 2016: Maria Estela Karolina, Floera Finalita, Victor Eliezer - Maria Estela Karolina (Jurnal Psikologi Jambi, 2018)
INTRODUCTION Depression is a psychiatric disorder that most often appears in patients with Diabetes Melitus (DM). Depression is one of the precipitating factors in diabetic patients because depression can raise blood glucose levels. On the other hand, psychological stress can arise when a person suffers from diabetes because they assume that the DM disease will cause a lot of problems. If DM is not handled properly, it will lead to various complications, one of the most common complications is diabetic foot. In a research it has been found that depression was associated with doubled increased risk of diabetic foot among patients with DM. METHODThis research used analytical research method with cross sectional approach. The sample was taken by Consecutive Sampling (15 patients with DM and 15 patients with foot ulcers). This research took place at RSUD Raden Mattaher Jambi from August to October 2016. The data were collected from direct interview with respondents included the identity of respondents and 21 questions BDI questionnaire. RESULTThe results showed that most of the patients with DM had normal score (53,3%) and fewest patient (6,7%) had severe depression score. On the other hand, most of the patients with foot ulcers had moderate depression score and no patient had normal score. The results of bivariate analysis showed that p-value = 0.000. CONCLUSION DAN RECOMMENDATIONFrom the data it can be concluded that there was a depression score comparison between patients with DM and patients with foot ulcers at RSUD Raden Mattaher Jambi in 2016. Keywords : Diabetes mellitus, diabetic foot, depression scores